Histochemistry as a versatile research toolkit in biological research, not only an applied discipline in pathology - Carlo Pellicciari (European Journal of Histochemistry, 2018)
The impressive progress of histochemistry over the last 50 years has led to setting up specific and sensitive techniques to describe dynamic events, through the detection of specific molecules in the very place where they exist in live cells. The scientific field where histochemistry has most largely been applied is histopathology, with the aim to identify disease-specific molecular markers or to elucidate the etiopathological mechanisms. Numerous authors did however apply histochemistry to a variety of other research fields; their interests range from the microanatomy of animal and plant organisms to the cellular mechanisms of life. This is especially apparent browsing the contents of the histochemical journals where the articles on subjects other than pathology are the majority; these journals still keep a pivotal role in the field of cell and tissue biology, while being a forum for a diverse range of biologists whose scientific interests expand  the research horizon of histochemistry to ever novel subjects. Thus, histochemistry can always receive inspiring stimuli toward a continuous methodological refinement.